2007
DOI: 10.1518/001872007x249884
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomic Evaluation of the Ambulance Interior to Reduce Paramedic Discomfort and Posture Stress

Abstract: The suggested practical layout contains four main modifications: (a) replacing the bench with two adjustable paramedic seats, (b) redesigning the medical cabinet for easy access, (c) adding an adjustable folding seat opposite the two new seats, and (d) adding a swiveling base and lifting apparatus that will accommodate the stretcher and enable better accessibility to patients by the paramedic personnel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 7 publications
0
27
0
4
Order By: Relevance
“…Research on ambulance-crash-related injuries has shown that EMS workers riding in the patient compartment of the ambulance wear their seat belt less than 50 percent of the time (Smith, 2003). This was confirmed by surveys conducted by Gilad and Byran (2007), in which only 3 percent of EMS workers reported always wearing their seatbelt.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…Research on ambulance-crash-related injuries has shown that EMS workers riding in the patient compartment of the ambulance wear their seat belt less than 50 percent of the time (Smith, 2003). This was confirmed by surveys conducted by Gilad and Byran (2007), in which only 3 percent of EMS workers reported always wearing their seatbelt.…”
Section: Introductionmentioning
confidence: 58%
“…Another factor contributing to low restraint compliance is that the seat used by paramedics is often in a poor location for providing patient care (Gilad and Byran, 2007). If the medic must access equipment on the far wall, he or she may need to lean over the patient or kneel at the side of the cot.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of workplace dimensions and the interaction between the environment and the human factor was approached by [12]. They showed that awkward and uncomfortable body postures are adopted as a result of the workspace layout and dimensions.…”
Section: Biomechanical Studymentioning
confidence: 99%
“…Ferreira and Hignett reviewed the layout of the patient compartment of a British ambulance; they found that future patient compartment design should consider health, comfort and performance [6]. Gilad and Byran found a clear association between perception of subjective discomfort inside the ambulance and common variables [7]. Their findings showed that the interior design was based primarily on spatial use with little concern for ergonomics.…”
Section: Introductionmentioning
confidence: 99%